H. Vashchenko’s Philosophy of Education in the Context of Contemporary Social and Cultural Transformations in Ukraine - Dovbnya, Viktor (Filosofiya osvity. Philosophy of Education, 2014)
The article is devoted to the analysis of the subject field of H. Vashchenko’s philosophy of education and the issue of cultural and educational legacy in the modern society. The possibilities of a new “reading” of Ukrainian thinker’s philosophical and pedagogical legacy are shown. The basic landmarks of H. Vashchenko’s philosophical and educational thought are illuminated: the arrangement of Ukrainian educational system, the unity of Ukrainian people, the approval of the independent Ukrainian state. The author of the article argues that a new paradigm of education should be developed on the basis of ideas of human, society, culture integrity and their proportional changes under the influence of transformation processes.